Parenting and Adolescents' Depressive Symptoms: The Mediating Role of Future Time Perspective. Issue 7 (3rd October 2017) - Diaconu-Gherasim, Loredana R.; Bucci, Colleen M.; Giuseppone, Kathryn R.; Brumariu, Laura E.
ABSTRACT: This study investigated the relations between maternal and paternal rearing practices and adolescents' depressive symptoms, and whether time perspective in adolescence explains these links. The sample included 306 students (158 girls), aged between 10.83 and 14.42 years. Adolescents completed questionnaires assessing their perceptions of maternal and paternal acceptance and psychological control, and of their future time perspective and depressive symptoms. Adolescents who rated their mothers as more accepting and those who rated their fathers as less psychologically controlling also reported lower levels of depressive symptoms and greater future time perspective. Further, adolescents who had greater future time perspective reported lower levels of depressive symptoms. Finally, time perspective partially mediated the relations of maternal and paternal acceptance, and paternal control with depressive symptoms in adolescence. The findings highlight the unique relations of maternal acceptance and paternal psychological control with adolescents' depressive symptoms, and that future time perspective is one mechanism that might explain why parenting strategies are linked with depressive symptoms in adolescence.